Bladder endometriosis – diagnostic and management challenges: A case report (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Urinary tract endometriosis (UTE) is the presence of endometriotic implants in the bladder,ureter, kidneys, or urethra. It affects ~1% of women with endometriosis and occurs more commonlyamong those with deep infiltrative endometriosis. Bladder endometriosis is the most commonpresentation, comprising 85% of cases. Concomitant involvement of the bladder and ureter is rare,comprising 1.4% of all cases. The clinical presentation involves lower urinary tract symptoms, thatworsen during menses. Timely diagnosis and treatment are crucial in ameliorating symptoms andpreventing complications, such as obstructive nephropathy. This is a case of bladder endometriosis withureteral involvement, outlining management challenges, reviewing evidence on managementapproaches, and highlighting the experience gained from this case in managing complex UTE.Case presentation: A 38-year-old female presented with a longstanding history of pelvic pain, dysuria,and new-onset voiding difficulty. She had undergone two prior surgical procedures for endometriosis,including a total abdominal hysterectomy. Her physical examination was normal. Ultrasound revealed a3-cm intracavitary bladder mass, which was described as likely endometriosis on magnetic resonanceimaging. On cystoscopy the mass was noted to be larger, encasing the left ureteric meatus. Alaparoscopic cystostomy was performed, with partial resection of the mass and placement of a temporaryureteric stent. After three months of medical treatment with dienogest, cystoscopy revealed a significantreduction in size with sub-centimeter residual avascular tissue. This was resected avoiding the ureter andureteric meatus. A new ureteric stent was placed. A repeat cystoscopy three months later revealed goodhealing with no residual endometriosis. The stent was removed, and a retrograde pyelogram confirmedno meatal stenosis or ureteric obstruction. She has remained symptom-free.Conclusion: Medical and surgical options are available for bladder endometriosis, with partialcystectomy being the gold standard. The initial approach is dependent on the size of the lesion and theextent of ureteric involvement. A staged approach that combines medical or surgical management canensure optimal outcomes while reducing surgery-associated morbidity in complex cases.